Adsorption of Cr(VI) on nano Uio-66-NH2 MOFs in water. Issue 15 (3rd August 2018) - Wu, Shibiao; Ge, Yejun; Wang, Yaqin; Chen, Xia; Li, Feifei; Xuan, Han; Li, Xi
ABSTRACT: An efficient adsorbent, nano Uio-66-NH2 Metal-organic frameworks (MOFs), for the high efficiency removal of Cr(VI) from aqueous solution was successfully synthesized. The adsorbent was characterized and its performance in Cr(VI) removal was evaluated for the first time. Kinetic data reveal that the Cr(VI) adsorption is rapid in the beginning followed by a slower adsorption process; The Cr(VI) adsorption kinetics were well described by the pseudo-second-order kinetics model. The calculated adsorption capacity of this adsorbent for Cr(VI) by Langmuir model was 32.36 mg/g at pH 6.5. The temperature-dependent isotherms indicated that the adsorption reaction of Cr(VI) on the MOFs was a spontaneous process. Filtration experiments revealed that the membranes fabricated by the MOFs could quickly remove Cr(VI) ions from the aqueous solutions. Electrostatic attraction between Uio-66-NH2 and Cr(VI) should be the mechanism for Cr(VI) adsorption by Uio-66-NH2 .